(u−2)(8u+1)(4u−8) выполните умножение

denis2013den denis2013den    1   27.09.2019 05:40    0

Ответы
annauskova21 annauskova21  10.09.2020 17:36

(u-2)(8u+1)(4u-8) = (8u^2+u-16u-2)(4u-8) = (8u^2-15u-2)(4u-8) =

32u^3-64u^2-60u^2+120u-8u+16 = 32u^3-124u^2+112u+16

ответ 32u^3-124u^2+112u+16

ПОКАЗАТЬ ОТВЕТЫ
Yyyyyyshdvjfc Yyyyyyshdvjfc  10.09.2020 17:36

(u-2)(8u+1)(4u-8) = (8u^2+u-16u-2)(4u-8) = (8u^2-15u-2)(4u-8) =

32u^3-64u^2-60u^2+120u-8u+16 = 32u^3-124u^2+112u+16

ответ 32u^3-124u^2+112u+16

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра